Inovação e Sustentabilidade: avaliação de projetos socioambientais financiados - Lopes, Liliane Duran (2020)
The movement for transition to a more sustainable economy is characterized by the necessity of searching innovative solutions in order to preserve the natural resources and reduce environmental and social impacts. In this sense, innovation takes on a prominent role as a great allied of sustainability, while socioenvironmental projects represent a way of transforming the reality of local groups towards sustainable development. Due to the intrinsic characteristics of innovation, uncertainties, risks and delay in return on investments, the financing for innovation requires specific lines of credits. Moreover, the support to socioenvironmental projects by forprofit organizations is another way of promoting the dissemination of better practices and better life conditions for people through innovative initiatives developed in association with public and/or private institutions. This research proposed the evaluation of aspects of innovative character and contribution for sustainability of socioenvironmental projects financed by the CAIXA Socio-Environmental Fund CAIXA (FSA CAIXA). In order to do so, a qualitative approach investigation was carried out, in which it was employed a strategy of multiple case studies on four socioenvironmental finalized projects that have been financed by FSA CAIXA in Parana district of Brazil. To this end, a qualitative approach investigation was carried out, using the multiple case study strategy with four completed socio-environmental projects that were financed by FSA CAIXA in the state of Parana. Interviews with representatives of each project (total of 04 groups) and beneficiaries (total of 02 groups) were conducted. The authors then proceeded to analyze documents produced during the project stages of data collection, work plan and final accountability reports, with the aim of triangulation of data in between these evidences. The data analysis was carried out considering categories and components obtained from literature that relate to innovation and to the three dimensions of sustainability. The results allowed contextualizing of the scenarios in which socioenvironmental projects are developed, as well as identify their innovative and sustainable characteristics. It was concluded that partnerships and financial support are indispensable in order to achieve sustainable development goals in the vulnerable communities served by these projects. It was also verified that the initiatives offered mainly activities for professional qualification, which had the focus of promoting work and increase in income in order to improve the quality of life of people. This goes to demonstrate a lack of public policies in the studied areas, as well as a prominence of the economic and social dimensions in comparison to the environmental dimension in the development of the projects. Therefore, it was found that the projects that presented most innovative characteristics were the ones that also presented more contributions among the sustainability dimensions, a fact that evidences the relationship between innovation and sustainability as well as the contribution of the present work. As a practical contribution, this study presents useful items related to sustainability and innovation for different funding funds to evaluate the initiatives to be supported, and also contributes to the dissemination of best practices to be reapplied by other projects, always with the aim of improving the direction of the use of physical and financial resources for sustainable development.